The bending-shear behaviors of steel reinforced fast-growing poplar glulam beams with different shear-span ratios. (20th September 2021) - Wang, Yuzhuo; Hou, Qian; Xu, Tiangui; Qu, Shuang; Zhang, Bingjie
Highlights: Bending-shear test of steel reinforced fast-growing poplar glulam was carried out. The failure modes of steel reinforced fast-growing poplar glulam beams with different shear span ratios were flexural failure or interlaminar shear failure. The steel reinforced fast-growing poplar glulam improved bearing capacity, stiffness and ductility. Theoretical models were proposed to calculate flexural and shear capacity. Abstract: A new type of steel reinforced fast-growing poplar glulam beam was proposed to improve the mechanical properties of fast-growing poplar glulam beam in this paper. 8 specimens were tested by a four-point bending method. The test was considered two factors: material properties (fast-growing poplar glulam beam, steel reinforced fast-growing poplar glulam beams) and shear-span ratios (1.5, 2, 2.5, 3, 3.5, 4, 6). Test results showed that: (1) The failure mode of the fast-growing poplar glulam beam was interlaminar shear failure. (2) When shear-span ratio (a/h) was between 3 and 6, the failure modes of the steel reinforced fast-growing poplar glulam beams were flexural failure; when shear-span ratio (a/h) was between 1.5 and 2.5, the failure modes of all steel reinforced fast-growing poplar glulam beams were interlaminar shear failure. (3) Compared with the fast-growing poplar glulam beam, the ductile coefficient, the ultimate load, the ultimate displacement and the initial bending stiffness of the steel reinforced fast-growing poplar glulam beams was increased by 92%, 34.7%, 64.7% and 60.9%, respectively. (4) With the increase of a/h, the ultimate load and the initial bending stiffness of the steel reinforced fast-growing poplar glulam beams decreased gradually, while the ultimate displacement and the ductile coefficient decreased first and then increased. Finally, the theoretical model is respectively proposed to estimate the flexural and shear capacity of the steel reinforced fast-growing poplar glulam beams.